The Arabi Spice Coffee as a Media of Culture: A Legacy of Social Cohesion and Generational Dynamics in Kampung Melayu, Semarang - Ahmad Fauzan Baihaqi; Chelsi Nadifa Kumala; Lathifah Aini; Revalina Ela Putri K (Insaniyat: Journal of Islam and Humanities, 2026)
This paper explores the tradition of drinking Arabian spice coffee at Menara Layur Mosque in Kampung Melayu, Semarang, Indonesia, as a cultural practice rich in philosophical values that go beyond beverage consumption. The tradition, which takes place during Ramadan, symbolises brotherhood, togetherness and multicultural heritage in a region inhabited by Arabs, Chinese and Indians. Serving Arabian spice coffee with dates and snacks after breaking the fast strengthens social bonds within the Muslim community. From a spiritual perspective, Drinking Arabian spice coffee plays an important role in Islamic traditions, especially Sufi practices, to maintain consciousness during nightly worship. Using observation and critical history methods, this study found that this tradition embodies hospitality and respect in Arab and Islamic culture. However, preserving this tradition faces intergenerational challenges, with some younger members feeling less engaged or unfamiliar with the practice. This study aims to explore the symbolic meanings, cultural values, and preservation efforts of the Arabian spice coffee tradition at Layur Tower Mosque by using a qualitative approach and historical methods. The research findings highlight the harmonious blend of social, spiritual, and cultural values that make up the identity of the local community and the importance of maintaining this tradition as part of the local cultural heritage.